A Course in Field Theory - van Baal, Pierre (Taylor & Francis, 2014)
Extensively classroom-tested, A Course in Field Theory provides material for an introductory course for advanced undergraduate and graduate students in physics. Based on the author's course that he has been teaching for more than 20 years, the text presents complete and detailed coverage of the core ideas and theories in quantum field theory.